Ibn al-Fāriḍ wa Ramz al-Madāma fi al-Qasīda al-Khamriyya - Herdiansyah, Pradibyo; Wardani, Yani‘ah; Hashif Ulwan , Ahmad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
This research delves into the symbolism within Ibn al-Fāriḍ's Qaṣīdah Khamriyyah, a prominent Sufi poem from the 14th century that utilizes wine as a metaphor for spiritual experiences. The poem reinterprets wine beyond mere intoxication, likening it to the ‘holy water’ mentioned in the Qur'an, specifically the Zanjabīl and Salsabīl springs in paradise. Ibn al-Fāriḍ views wine as an essential element for a sālik (seeker) striving for unity with the Divine Beloved, marking the peak of their spiritual journey. This study uncovers the philosophical and symbolic layers of wine's descriptions in the poem by linking textual analysis with interpretative commentary. Ultimately, it argues that Ibn al-Fāriḍ's work transcends aesthetic beauty, offering profound insights into mystical experiences and the pursuit of divinity within Sufism, enriching our understanding of spiritual symbolism in his poetry. Contribution: This research contributes new insights into the understanding of the intricate relationship between the aesthetic beauty of Ibn al-Fāriḍ’s poetry and its profound mystical meanings. It enhances understanding of spiritual experiences and the pursuit of the Divine in Sufism, positioning Ibn al-Fāriḍ as a masterful poet and a significant thinker in the quest for unity with the Beloved.